THE RELATIONSHIP BETWEEN MOTIVATION WITH OBEDIENCE TO VISITS THE ELDERLY’S INTEGRATED HEALTH CARE IN PATIENTS WITH ARTHRITIC(STUDY IN THE KLAGEN HAMLET, KEMBENG KEPUH VILLAGE, DISTRICT PETERONGAN, JOMBANG) - Teguh Heri Setiyawan; Hidayatun Nufus; Dwi Prasetyaningati (STIKES Insan Cendekia Medika Jombang, 2012)
Elderly with arthritic requires a proper motivation to rise willingness of elderly to follow the activities ofelderly’s integrated health care. The purpose of this research is analyze the relationship betweenmotivation with obedience to visits the elderly’s integrated health care in patients with arthritic in theKlagen Hamlet, Kembeng Kepuh Village, District Peterongan, Jombang. This research use analyticaldesign with cross sectional approach. The population is all elderly with arthritic in the Klagen Hamlet,Kembeng Kepuh Village, District Peterongan, Jombang with the sample is 44 people using purposivesampling technique. The independent variable is motivation and dependent variable is the obedience tovisits elderly integrated health care in patients with arthritic. The instrument is questionnaires andprocessing by editing, coding, scoring, tabulating and statistical test using spearman rank test. Results ofthe study showed the elderly’s motivation to visit elderly’s integrated health care in patients with arthriticis mostly strong (61.4%) and most of the obedience to visit elderly’s integrated health care is obedient(61.4%). Spearman rank test showed that significant value  = 0.000 < (0.05), so that H1 is accepted.The conclusion of this research stated that there is a relationship between motivation with obedience tovisits elderly’s integrated health care in patients with arthritic in the Klagen Hamlet, Kembeng KepuhVillage, District Peterongan, Jombang. The research can be used as reference to conduct elderly to staymotivated and obedient in visit elderly imtegrated health center so that the elderly can cure they’rerheumatism disease.